An investigation of the individual investors in the Turkish securities market - Türkeş, Derya. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1986., 1986)
In this thesis, differences between the two individual investor groups - bondholders and common stockholders- in their demographic characteristics, basic portfolio objectives, information sources and decision mechanics, instrument selection criteria and market attitudes, and return perceptions have been studied. It has also been possible to find out a general profile of the individual investor in the securities market. The study included the literature review and a fiel d study which was conducted through a questionnaire. Data was analyzed and the findings were given together with the implications for the marketers and researchers. The findings of the study showed that same significant differences exist in investment processes of the individuals rather than their demographic characteristics. Bondholders appeared to be more educated and relatively older than the commonstockholders. They have fixed monthly income and invest relatively greater proportion of their income in securities, mostly seeking "safeness" of investment and "additional income" for their family budget. Commonstockholders, on the other hand, being more independent in their decisions invest mainly for protecting their money from inflation and capital appreciation. They are also slightly less sensitive to the IIsafeness" of investment than their counterparts and emphasize such factors as liquidity of investment, anonimity of investor and tax considerations when choosing among securities. Knowledge of these differences should help bank and brokerage firms' managers, and researchers to better understand the individual investor and his investment process and to allocate their marketing effort more effectively .
Keywords: Stock exchanges -- Turkey.; Investments.